Does the first generic exclusivity system provide an economic incentive for early generic entrance under the patent linkage system? - Kyung-Bok Son (Frontiers Media S.A., 2023)
IntroductionA period of exclusivity for the first generics, as part of the patent linkage system, was established in South Korea to provide an economic incentive for early generic entry. This study describes the dynamics of generic penetration and assesses the first mover market share advantages under the patent linkage system.MethodsPairs of originators and their corresponding generics granted the first generic exclusivity from 2015 to 2020 were identified. We categorized generics into first movers and latecomers, described the penetration curves of generics, and estimated the saturated market share of generics, first movers, and latecomers. Volume-based monthly prescriptions were used to describe the generics' penetration curves. A logistic growth model was adopted to estimate the saturated market shares of generics.ResultsWe identified 28 pairs of originators and generics, presented penetration curves, and estimated generics market shares. The saturated market share of generics was 30%, and the time to saturation was approximately 33 months. The shapes of penetration varied by nationality, route, and number of generics. The existence of latecomers was associated with the decreased penetration speed over time and decreased market share of generics. However, the first mover market share advantages or latecomers' disadvantages were consistently observed.ConclusionThe generic uptake in South Korea is delayed, limited, and context-dependent. However, first generics' market share advantage suggests that a period of exclusivity, as part of the patent linkage system, could provide an economic incentive for early generic entrance.